Comparison of efficacy, pharmacokinetics, and immunogenicity between infliximab mono‐ versus combination therapy in ulcerative colitis. Issue 6 (June 2014) - Hayes, Michael J; Stein, Adam C; Sakuraba, Atsushi
Abstract Background The association of concomitant immunosuppressant use with infliximab (IFX) and therapeutic outcomes in correlation with pharmacokinetic properties in ulcerative colitis (UC) remains unclear. Aims To assess the effect of concomitant immunosuppressant use on the duration of IFX therapy, and the pharmacokinetic properties of IFX in patients with UC. Methods A retrospective analysis of UC patients treated with IFX. Duration of efficacious IFX therapy, and serum IFX and antibody‐to‐IFX (ATI) levels were compared between those receiving IFX as monotherapy and in combination with an immunosuppressant. Results Among the 85 UC patients who received IFX, 46 (54.1%) received concomitant immunosuppressants, and 38 (45.9%) received IFX monotherapy. Concomitant immunosuppressant use was associated with increased duration of IFX therapy as 90% of patients receiving immunosuppressants remained on therapy at 1 year versus 61% of patients on monotherapy (Log‐rank, P = 0.016). Concomitant immunosuppressant use, as compared with monotherapy, was associated with greater IFX levels (20.4 mg/L vs 10.5 mg/L, P = 0.025) and less frequent ATI formation (4.5% vs 33.3%, P = 0.031). Patients receiving greater than 2.0 mg/kg of azathioprine had greater IFX levels than those receiving less than 2.0 mg/kg (26.0 vs 10.6 mcg/mL, P = 0.03) and those receiving IFX monotherapy (26.0 vs 11.2 mcg/mL, P = 0.03). The duration of IFX therapy among patients receiving less than 2.0 mg/kg azathioprine was indistinguishable from patients on IFX monotherapy (Log‐rank, P = 0.95). Conclusion Concomitant immunosuppressant therapy with IFX improves outcomes in UC as shown by increased duration of therapy, decreased immunogenicity against IFX, and increased blood levels of IFX. Our data suggest that this benefit may be dependent on the dose of concomitant immunosuppression.